Beyond slash and burn: building on indigenous knowledge in managing Borneo’s tropical rain forests - Colfer, C.J.P.; Peluso, N.L.; Ching See Chung (New York Botanical Garden Press, 1997)
This book contains contributions from a variety of authors including forest dwellers themselves, describes the natural resource management system of the Uma’ Jalan Kenyah people of East Kalimantan, Indonesia. Colfer and her co-authors seek to present the knowledge of the local people about their surrounding forest and its sustainable management in a way that trained scientists will understand and use. The people and their knowledge of the forest are seen as an integral part of the biodiversity of the forest. The rapid loss and degradation of humid tropical rain forests over recent years has meant that the unique ways of life of those people who live in and from these forests are threatened. The urban and agricultural settings that usually succeed forest clearing are not conducive to preserving the knowledge and cultures that have developed over centuries. By introducing the ways in which the Uma’ Jalan perceive their natural resources, then focussing on their agroforestry system from this viewpoint, the subsistence base of these forest dwellers is explored. The role of money in such a system is defined and options available to the people for survival described. In the final chapter the ramifications of these findings for forest management in the tropics is discussed with emphasis on how Uma’ Jalan customs might be adapted to preserve at least part of the forest environment for conservation, for biodiversity, improved subsistence for small populations and sustainable timber extraction.